Sistem Bilik Steril Dengan Perangkat Mist Maker Dan Arduino Uno Menggunakan Metode Sekuensial Linier - Zakaria, Hadi; Febiyanto, Dedy; Rosyani, Perani (Forum Kerjasama Pendidikan Tinggi, 2022)
Lintas Era Digital is a company engaged in the business of Technology Development as a School Vendor to work on various difficulties in schools within the scope of information technology such as Websites, Computer Based Test (CBT) Applications, Learning Management System (LMS) Applications and Electronic Cases, CCTV, Computers, laptops and procurement of tools for the prevention of Covid-19 that use electronic elements. The problem that is being faced by this company and from some current clients is the Covid-19 prevention tool that is still not in accordance with health protocols, there are still many shortcomings that are currently being faced, one of which is the Sterilization System using sterile booths automatically using a microcontroller. To overcome the problems above, it can be used a tool in the form of a microcontroller using several sensors such as a PIR Sensor (Passive Infrared Sensor) and using a Mist Maker tool (condensing device). The goal is to facilitate the performance of sterilization. In this study the author uses the C programming language.With a sterilization system using this microcontroller, it can help the community to find it easy to carry out health protocols. To be able to run this microcontroller, the author makes settings for the tool so that people can directly use the tool.